Alchemy : synthesis and sound design with Alchemy in Logic Pro X - Dvorin, David (Peachpit Press, 2016)
Introduced in Logic Pro 10.2, Alchemy joins the upper echelon of sound design tools offered by Logic Pro. Filling the gap between sampling and synthesis, Alchemy is uniquely positioned, providing Logic users with novel ways to create heretofore-unheard sounds and instruments. By combining such advanced sound generation technologies as granular, spectral, and additive synthesis, Alchemy allows you to manipulate audio to unprecedented levels. In Synthesis and Sound Design with Alchemy in Logic Pro X , you will gain familiarity with Alchemy by exploring the interface, sound engines, and control paradigms, which will give you an extraordinary vehicle for getting “inside” sound and making your own unique instruments. Includes: Authoritative explanations of the user interface and source elements Instructions show you how to mix multiple sources and use the Arpeggiator Lesson review questions to summarize what you learn.